Distance-dependent danger responses in bacteria. (April 2017) - Westhoff, Sanne; van Wezel, Gilles P; Rozen, Daniel E
Highlights: Bacteria respond differentially to cues from competitors at different distances. Volatile compounds induce mechanisms of escape, including antibiotic resistance. Diffusible molecules from closer competitors induce antibiotic production. Cell-contact mediated antagonism results in immediate counterattack. Abstract : The last decade has seen a resurgence in our understanding of the diverse mechanisms that bacteria use to kill one another. We are also beginning to uncover the responses and countermeasures that bacteria use when faced with specific threats or general cues of potential danger from bacterial competitors. In this Perspective, we propose that diverse offensive and defensive responses in bacteria have evolved to offset dangers detected at different distances. Thus, while volatile organic compounds provide bacterial cells with a warning at the greatest distance, diffusible compounds like antibiotics or contact mediated killing systems, indicate a more pressing danger warranting highly-specific responses. In the competitive environments in which bacteria live, it is crucial that cells are able to detect real or potential dangers from other cells. By utilizing mechanisms of detection that can infer the distance from danger, bacteria can fine-tune aggressive interactions so that they can optimally respond to threats occurring with distinct levels of risk.